Histology of the nasal conchae in mithun (Bos forntalis) and zebu (Bos indicus) - KALITA, H C; BHATTACHARYYA, R (The Indian Journal of Animal Sciences, 2014)
Histomorphological studies of the nasal conchae in mithun and zebu were recorded. The rostral part of the dorsal nasal concha in mithun and zebu revealed a non-keratinized stratitied cuboidal which gradually transformed into respiratory epithelium through a transitional zone. The epithelium of the middle nasal concha was also respiratory type in the entire cranial and middle part. the respiratory epithelium was transformed through a transitional zone caudally into olfactory epithelium. The rostral part of the ventral nasal concha revealed stratified squamous epithelium with a transitional zone into respiratory epithelium in its middle and caudal part. The whole area of ethmodial conchae possessed olfactory epithelium. The glands found in the lamina propria of all the conchae were of serous dominant in mithun and were sero-mucous in zebu.